2006
DOI: 10.1504/ijesd.2006.011557
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and the challenge of triple bottom line integration: insights from the Lebanese context

Abstract: The notion of sustainability has been evolving and is increasingly understood to encompass considerations of economic viability, as well as environmental sustainability and social responsibility. This paper examines how linking these three legs of sustainability remains a challenge and explores empirically the performance of a sample of Lebanese organisations in the three strands of responsibility. The findings suggest that organisations in a developing country context report challenges in maintaining a sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This also opens a question of inefficient budget spending, lack of stakeholder's awareness, disorientation in CSR strategy, poor prioritization and low innovativeness. Jamali et al (2006) found similar findings earlier in their research. Their conclusion is summarized as, "the problem faced in the Lebanese and other contexts is the absence of a precise management framework that provides for the linking of these fundamental, yet seemingly disparate pillars of sustainability and for reconciling traditional financial performance with environmental and social contributions" (p. 410).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This also opens a question of inefficient budget spending, lack of stakeholder's awareness, disorientation in CSR strategy, poor prioritization and low innovativeness. Jamali et al (2006) found similar findings earlier in their research. Their conclusion is summarized as, "the problem faced in the Lebanese and other contexts is the absence of a precise management framework that provides for the linking of these fundamental, yet seemingly disparate pillars of sustainability and for reconciling traditional financial performance with environmental and social contributions" (p. 410).…”
Section: Discussionsupporting
confidence: 90%
“…Societal CSR initiatives are ranked from 1 to 4 and from 6 to 7, while 5 and 8 are environmentally related. Such categorization does not fit the CSR Triple Bottom Line integration, whereby according to Jamali et al (2006), "the TBL approach is grounded in the simple realization that corporations can add value and should publicly account along three drivers, namely the economic, the environmental and the social drivers" (p. 399).…”
Section: Top 8 Csr Tool (Initiatives) Preference Ranked By Respondentmentioning
confidence: 99%
“…Emirates' managers are aware of green accounting which concentrates on CSR issues of environment; Hejase et al (2017) who asserted that Lebanese corporations concentrate their CSR activities or initiatives along two dimensions: societal philanthropic and environmental perspectives. Also, Jamali et al (2006) concluded that -the problem faced in the Lebanese and other contexts is the absence of a precise management framework that provides for the linking of these fundamental, yet seemingly disparate pillars of sustainability and for reconciling traditional financial performance with environmental and social contributions‖ (p. 410) and finally D'Amato, Henderson, and Florence (2009) stressed the fact that, -organizations are being called upon to take responsibility for the ways their operations impact societies and the natural environment‖ (p. 1).…”
Section: Csr Toward the Environmentmentioning
confidence: 99%
“…This result is consistent with those obtained by Saeedan (2017), Al-Maouchi (2016), andKhalidi (2015), which indicated that most of the CSR dimensions were averagely applied. Nevertheless, Jamali et al (2006) were right in their conclusion that there is an absence of a -precise management framework that provides for the linking of all CSR pillars‖ (p. 410). Similarly, Brin & Nehme (2019) ascertain that an organization must satisfy the surrounding society and respect its wellbeing by performing social activities, especially its employees and the surrounding community.…”
Section: Hypotheses Evaluationmentioning
confidence: 99%
“…Traditionally, the focus in business has been on financial performance and maximising profits (Tran 2015). However, there has been a shift in recent years towards focusing on environmental performance and sustainability of the triple bottom line (Jamali, Mezher & Bitar 2006). It is important for organisations to understand the negative impact their operations have on the environment and the potential of supply chains to contribute to reducing costs and harmful emissions.…”
Section: Problem Statementmentioning
confidence: 99%